2013
DOI: 10.1111/ijfs.12453
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, sensory and cooking quality evaluation of durum wheat spaghetti enriched with pea flour

Abstract: Summary The goal of the study was to obtain spaghetti enriched with pea flour with sensory properties close to conventional pasta. To this aim, the study has been organised in two subsequent trials. In the first, the pea flour amount added to the spaghetti was continuously increased until the overall sensory quality reached its threshold value (pea flour concentration = 15%). In fact, the spaghetti samples supplemented with 15% pea flour (15%S‐P) showed less elasticity, unpleasant colour and higher firmness co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 32 publications
4
59
1
4
Order By: Relevance
“…In terms of firmness no differences among samples were recorded, even though a little increase was found in pasta with fine particles because these particles contain more protein than coarse particles of tomato peels. Padalino [12] also found that the high protein content of pea flour increased pasta hardness due to low hydration of starch granules. Most probably, during cooking, the protein can link to most of the water molecules, leaving less water to swell the starch phase [24].…”
Section: Step 2 Effects Of Tomato Peels Particles Size On Spaghetti Qmentioning
confidence: 95%
See 3 more Smart Citations
“…In terms of firmness no differences among samples were recorded, even though a little increase was found in pasta with fine particles because these particles contain more protein than coarse particles of tomato peels. Padalino [12] also found that the high protein content of pea flour increased pasta hardness due to low hydration of starch granules. Most probably, during cooking, the protein can link to most of the water molecules, leaving less water to swell the starch phase [24].…”
Section: Step 2 Effects Of Tomato Peels Particles Size On Spaghetti Qmentioning
confidence: 95%
“…Subsequently, the pasta was dried in a dryer (SG600; Namad). The process conditions were in according Padalino [12].…”
Section: Spaghetti Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…A introdução de diferentes farinhas vem sido incluídas em sua formulação, proporcionando também uma funcionalidade nas farinhas utilizadas (Feitoza et al, 2014;Padalino et al, 2014;Sereewat et al, 2015;Vieira et al, 2015). A mais expressiva diferença entre os teores físico químicos analisados no macarrão tipo talharim é o teor de betacaroteno, como consequência da adição de 20% de farinha de batata-doce biofortificada em sua formulação.…”
Section: Farinha De Batata-doce Beauregard Punclassified